Investigation on temperature shrinkage characteristics of the combined structure in asphalt pavement - Jiangcai, Chen; Zhiwei, Li; Zihong, Zhao; Xiaofeng, Huang; Jie, Chen; Zhiyang, Liu (Frontiers in Materials, 2022)
Pavement cracking is primarily caused by the temperature shrinkage of materials. Current research mainly focuses on the temperature shrinkage of single materials. The object of this work is to analyzed the effect of structural combination on the temperature shrinkage. To this end, temperature rise method was first discussed to measure the shrinkage coefficient to replace traditional temperature drop method. Then, the temperature shrinkage coefficient of lime-fly-ash stabilized macadam, ATB and AC asphalt mixtures were measure. The effect of gradation types, lime-fly-ash content and nominal maximum aggregate size on the temperature shrinkage was studied. Finally, the temperature shrinkage of composite structure characteristic was analyzed. The results show that the difference between the temperature shrinkage coefficients obtained by temperature rise and drop methods was quite small. Thus, temperature rise method can be used to measure the temperature shrinkage coefficient. In addition, the lime-fly-ash stabilized macadam with the suspended dense gradation or higher lime-fly-ash content has the largest temperature shrinkage strain. It is suggested that the suspended dense gradation should be avoided and the content of lime-fly-ash should be approximately reduced to control the temperature shrinkage strain of simi-rigid base course. As for asphalt mixture, the temperature shrinkage strain increased with the decrease of the nominal maximum aggregate size. The asphalt mixture with larger nominal maximum aggregate size should be given priority to control the temperature shrinkage. Finally, when combined with base course or surface layer, the temperature shrinkage of base course was promoted by the surface layer, while the surface layer was inhibited by the base course. Meanwhile, the mutual influence between semi-rigid base course and surface layer was stronger than that of the mutual influence between flexible base course and surface layer.